Technology, social services and organizational innovation or how great expectations in London and Cardiff are dashed in Lowestoft and Cymtyrch. - Shaw, Ian; Morris, Kate; Edwards, Anne (Journal of Social Work Practice, 2009)
The purpose of this paper is to illuminate important aspects of the policy implementation process in UK welfare organizations. We draw on two evaluations in which we were each involved — those of the Integrated Children's System and the Children's Fund. Our interpretive frameworks share a concern to foreground the significance of the local, informal, and ground level, but do so in ways that acknowledge the encompassing governmental and policy contexts. We illustrate and assess the significance of multiple policy aspirations, the significance of local implementation contexts, the diverse ways in which practitioners gain and subsequently develop knowledge of how policy works, and how such knowledge moves about in organizations. We indicate the kinds of expertise that social service workers bring to and achieve as actors within policy innovations, and how they may manage and in some cases seek to control knowledge shifts between providers and users of services. We infer the inadequacy of conventional top-down models of implementing policy innovations.